REPRODUCTION MANAGEMENT OF SPECIALISTS ENSURING INNOVATION DEVELOPMENT OF THE NATIONAL ECONOMY IN BELARUS: THEORETICAL AND METHODOLOGICAL ASPECTS - E. V. Gurina; T. I. Serchenia (Наука и техника)
The paper justifies phases of specialists reproduction ensuring innovation development of the national economy in Belarus, -i.e. innovation activity managers. Realization of reproduction phases is presented within the system consisting of four blocks – target block, control block, controllable block and ensuring block. Solution of the problems pertaining to reproduction of innovation activity managers has been considered within the context of formation of organizational economic approaches to system management of their reproduction that presuppose usage of the process approach in every phase of the reproduction process.